Understanding Social Challenges: Perspectives on the United Nations Declaration on the Human Rights of Peasants and Rural Working Peoples - Muhammad Husni Thamrin; Nasution, Nabila Fahira (Talenta Publisher, 2024)
This research explores Peasants’ social challenges in Indonesia and UNDROP's response to these challenges. Challenges include limited access to resources and land, agrarian conflict, difficulty accessing adequate seeds, and economic uncertainty. UNDROP provides a vital framework to fight for Peasants’ rights, emphasizing land, seed, and food rights. A qualitative research method was used using the UNDROP perspective. Data was collected through primary and secondary sources and analyzed using data reduction, presentation, and conclusion-drawing methods. The results show the need for more vigorous law enforcement and better protection of Peasants’ rights. Efforts to address Peasants’ social challenges include the implementation of the Peasant Protection and Empowerment Act, providing financial and technical support, and implementing UNDROP by the government and various relevant parties. This study concludes that collaboration between the government, Peasant organizations, NGOs, and the international community is crucial in ensuring the protection and welfare of Peasants. Implementing UNDROP is crucial in ensuring Peasants’ rights are protected. This research contributes significantly to understanding the social challenges Peasants face in Indonesia and the efforts that can be made to address these challenges effectively.